MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI KINERJA GURU DI SMA NEGERI 1 CIBATU KABUPATEN PURWAKARTA - Yuniawati, Yuniawati; Erawan, Raden Dewangga Tresna; Habibie, M. Faiz; Yoseptry, Ricky (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
The principal's management ability is the most important factor in order to improve the quality and progress of the school. With the management, it is hoped that the principal can increase the motivation of teacher performance. Motivation of teacher performance certainly requires a strong role of the principal in planning, organizing, directing and controlling. The purpose of this study is to describe and analyze the principal's management regarding planning, organizing, directing and control. The purpose of this study is to describe and analyze the principal's management regarding planning, organizing, directing and controlling so as to increase the motivation of teacher performance in schools. This research uses a qualitative approach with a case study method. The source of this research data is primary data and secondary data. Data collection techniques through observation, interviews, and documentation. Analysis of research data is carried out through by Steps: (1) Collecting data, (2) Reducing data, (3) Exposure of data, and (4) drawing conclusions. The results of the study are: 1) The ability of the principal's management in planning teacher performance motivation at SMA Negeri 1 Cibatu; 2) The principal's management ability in organizing teacher performance motivation at SMA Negeri 1 Cibatu according to procedures; 3) The principal's management ability in directing teacher performance motivation at SMA Negeri 1 Cibatu has been running well; and 4) The ability of the principal's management in controlling or supervising to increase teacher performance motivation at SMA Negeri 1 Cibatu by monitoring and evaluating. From the overall management of the principal, it can be stated that the Principal of SMA Negeri 1 Cibatu Purwakarta Regency has been able to increase the motivation of teacher performance.